Alleviation of 1,N(6)-ethanoadenine genotoxicity by the Escherichia coli adaptive response protein AlkB - Frick, Lauren E. (National Academy of Sciences, 2007)
1,N(6)-ethanoadenine (EA) forms through the reaction of adenine in DNA with the antitumor agent 1,3-bis(2-chloroethyl)-1-nitrosourea, a chemotherapeutic used to combat various brain, head, and neck tumors. Previous studies of the toxic and mutagenic properties of the DNA adduct EA have been limited to in vitro experiments using mammalian polymerases and have revealed the lesion to be both miscoding and genotoxic. This work explores lesion bypass and mutagenicity of EA replicated in vivo and demonstrates that EA is neither toxic nor mutagenic in wild-type Escherichia coli. Although the base excision repair glycosylase enzymes of both humans and E. coli possess a weak ability to act on the lesion in vitro, an in vivo repair pathway has not yet been demonstrated. Here we show that an enzyme mechanistically unrelated to DNA glycosylases, the adaptive response protein AlkB, is capable of acting on EA via its canonical mechanism of oxidative dealkylation. The reaction alleviates the unrepaired adduct's potent toxicity through metabolism at the C8 position (attached to N1 of adenine), producing a nontoxic and weakly mutagenic N(6) adduct. AlkB is shown here to be a geno-protective agent that reduces the toxicity of DNA damage by converting the primary adduct to a less toxic secondary product.